Penyuluhan Tentang Dampak Pernikahan Dini pada Remaja Putri di Desa Darul Amin Kecamatan Lawe Alas Kabupaten Aceh Tenggara - Yessy Syahradesi Br Tambunan; Purnama Sari Cane; Fika Lestari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
A human being was created to live in pairs as husband and wife through marriage. Marriage is a spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family or household. Ideally, women marry at the age of 21-25 years, while men at the age of 25-28 years. It is recommended that getting married at this age can be done in terms of the health of the woman's reproductive organs, which are ready to conceive and give birth. Likewise, men of this age are ready to fulfill their obligations as head of the family (Fatmawati etal., 2019). This community service activity takes the form of counseling about the impact of early marriage on teenagers in Darul Amin Village, Lawe Alas District, Southeast Aceh Regency. This activity was attended by 30 participants with the aim of increasing young women's knowledge about the impact of early marriage on young women. The results of this activity were an increase in the knowledge of young women before and after being given counseling, namely from an average knowledge score of 50 to 80. It is hoped that this activity can be useful for young women and not to engage in early marriage to prevent the effects, namely miscarriage, anemia, birth weight low, sexually transmitted diseases.